PSYCHOLOGICAL WAYS TO OVERCOME PROFESSIONAL STRESS IT EMPLOYEES OF COMPANIES (Psychology Travelogs, 2024)
The article presents the results of an empirical study of the peculiarities of the manifestation of professional stress among employees of IT companies. The most vulnerable components of its manifestations in the studied respondents were determined. The substantiation of the author's Program for psychological support of professional health of employees of IT companies (hereinafter the Program) was carried out. The construction of the Program was based on the principles of creating a healthy and productive working atmosphere for members of professional teams, promoting the preservation of health and well-being of employees, among which the priority was given to: reducing the risk of occupational diseases, improving the quality of life in ontogenesis and professionogenesis, improving labor productivity, reducing the percentage of losses working hours, forming a positive image of the company on the labor market, creating a healthy and successful professional environment for employees.The advantage of the implemented Program is that, for the first time, elements of nutritional correction were applied in the set of measures of health-saving technologies, the peculiarities of nutrition were studied and recommendations were developed for the formation of nutritional hygiene of the company's employees, in the set of measures aimed at prevention and reducing the impact of professional stress on the personality of employees.Psychological diagnosis of the determinants of professional health of the examined respondents was carried out according to direct and indirect indicators using a set of developed methods, which were used at the ascertaining stage, which provided for the identification of psychological features of the manifestation of professional stress in employees and the formative one, which was used to check the effectiveness of the developed author's Program.Based on the obtained results, five factors were singled out, which we can consider as a psychological determinant of the manifestation of professional stress: F1 typological; F2 – motivational; F3 – adaptive; F4 – communicative; F5 – emotional and volitional self-regulation.
Keywords: professional health; professional stress; professional burnout; employees of IT companies; professional profile; psychographic profile